PERFORMANCE OF DAIRY STEERS SUPPLEMENTED PASTURE DURING THE TRANSITION PERIOD WATER-DRY - Brandão; R. K. C.; G. G. P.Carvalho; R. R.Silva; D. L. S.Dias; J. O. Guimaraes; T.O.J. D’A.Lins; M.M.S.Pereira; V.M.Carvalho; M.M.Lisboa; D.S.Barroso; L. M. A. Rufino (Journal of Animal and Plant Sciences, 2016)
The aim of this study was to evaluate the effects of protein-energy or mineral supplementation on the digestibility and productive performance of steers in the post-weaning phase on pasture during the wet-dry season transition. Twenty-two Holstein-Zebu crossbred steers with an average initial weight of 234.5 ± 16.0 kg were used in the experiment. The following treatments were tested: protein-energy supplementation (0.4% of the body weight) and mineral supplementation ad libitum. The intake of total dry matter, organic matter, neutral detergent fiber corrected for ash and protein, and crude protein increased they were higher (P <0.05) for the group receiving protein-energy supplement than group that consumed only mineral salt. The digestibility of dry matter, organic matter, and crude protein increased (P<0.05) for the group receiving protein-energy supplement when compared to the group of animals that consumed mineral salt. The average daily gain and total weight gain were higher (P <0.05) for the group of animals that received protein-energy supplement which received mineral supplement.The use of protein-energy supplementation during the wet-dry season transition improves the nutritional and productive performance of dairy steers on Brachiariabrizantha pastures.
Keywords: cattle; feed conversion; grazing; supplementation; weight gain